Lync Server cookbook : over 90 recipes to empower you to configure, integrate, and manage your very own Lync Server deployment /: over 90 recipes to empower you to configure, integrate, and manage your very own Lync Server deployment. (2015) - Volpe, Fabrizio
No abstract available